Cell cycle re-entry sensitizes podocytes to injury induced death. Issue 14 (17th July 2016) - Hagen, Manuel; Pfister, Eva; Kosel, Andrea; Shankland, Stuart; Pippin, Jeffrey; Amann, Kerstin; Daniel, Christoph
ABSTRACT: Podocytes are terminally differentiated renal cells, lacking the ability to regenerate by proliferation. However, during renal injury, podocytes re-enter into the cell cycle but fail to divide. Earlier studies suggested that re-entry into cell cycle results in loss of podocytes, but a direct evidence for this is lacking. Therefore, we established an in vitro model to test the consequences of re-entry into the cell cycle on podocyte survival. A mouse immortalized podocyte cell line was differentiated to non-permissive podocytes and stimulated with e.g. growth factors. Stimulated cells were analyzed for mRNA-expression or stained for cell cycle analysis using flow cytometry and immunocytofluorescence microscopy. After stimulation to re-entry into cell cycle, podocytes were stressed with puromycin aminonucleoside (PAN) and analyzed for survival. During permissive stage more than 40% of immortalized podocytes were in the S-phase. In contrast, S-phase in non-permissive differentiated podocytes was reduced to 5%. Treatment with b-FGF dose dependently induced re-entry into cell cycle increasing the number of podocytes in the S-phase to 10.7% at an optimal bFGF dosage of 10 ng/ml. Forty eight hours after stimulation with bFGF the number of bi-nucleated podocytes significantly increased. A secondary injury stimulus significantly reduced podocyte survival preferentially in bi-nucleated podocytes In conclusion, stimulation of podocytes using bFGF was able to induce re-entry of podocytes into the cell cycle and to sensitize the cells for cell death by secondary injuries. Therefore, this model is appropriate for testing new podocyte protective substances that can be used for therapy.